Impact of Hepatic Cirrhosis on Outcome in Adult Cardiac Surgery - Dimarakis, Ioannis; Grant, Stuart; Corless, Rebecca; Velissaris, Theodore; Prince, Martin; Bridgewater, Ben; Asimakopoulos, George (The Thoracic and Cardiovascular Surgeon, 2015)
Increasing prevalence of hepatic disease is likely to translate in a growing number of patients with significant hepatic disease requiring cardiac surgery. Available cardiac risk stratification models do not address the risk associated with hepatic disease. However, weighted mean mortality rates based on previous studies of cardiac surgery in patients with hepatic disease demonstrate operative mortality rates that range from 9.88% (standard deviation [SD] 9.69) for patients in Child–Turcotte–Pugh (CTP) class A cirrhosis to 69.23% (SD 28.55) for patients with CTP class C cirrhosis. This review comprehensively appraises the pathophysiology of hepatic disease, reported clinical outcomes and considerations for risk stratification.
Keywords: liver diseases/cirrhosis; risk; outcomes